A wetland ecosystem service assessment tool; Development and application in a tropical peatland in Uganda. (August 2019) - Langan, Charlie; Farmer, Jenny; Rivington, Mike; Novo, Paula; Smith, Jo U.
Graphical abstract: Highlights: Data for modelling tropical wetland ecosystem services is limited. A simple field survey and accounting methodology assesses wetland services. Assessment provides crude but useful assessment and data for further modelling. East Africa wetland soil, vegetation and hydrology properties are presented. Abstract: We present the methodological development of a surveying and accounting tool created in response to a lack of appropriate data for modelling ecosystem services in tropical wetlands in East Africa. The survey provides a practical field methodology for quickly characterising the environmental, vegetation, soil and hydrological properties of a wetland using a nested sample site and sub-plot procedure. The accounting procedure provides simple calculations for combing these survey data with literature values to estimate ecosystem services provided by the wetland. The wetland ecosystem service assessment is based on per unit area estimates by land cover type, and scaled by areal extent of each land cover. The tool was tested and deployed in 60 locations within the Kashambya wetland complex, southwest Uganda. Results of the survey and accounting procedure are presented along with data on wetland soil, vegetation and hydrological properties. Our results, showing standard errors, demonstrate that while the Kashambya wetland has been extensively modified by anthropogenic influences, it remains a large store of water (7.0 ± 1.3 m 3 ) and carbon (0.5 ± 0.04 M t). The wetland is a large source of water vapour (40 ± 180 k m 3  y −1 ) and sink for carbon (3 ± 4 k t y −1 ). The high uncertainty of flux estimates demonstrate the need for further biophysical modelling based upon the data captured by the survey tool. The wetland provides food production services valued as US$ 1 ± 0.1 M y −1 . Our results show that ecosystem services provided by wetlands change significantly under different land cover, but high heterogeneity of ecosystem service provision exists within land cover classes. Greater understanding of spatial dynamics is required to improve accuracy of wetland ecosystem service assessments, and to examine the implications of land management and climate change on wetland ecosystem services.